Anti-Saccharomyces cerevisiae antibodies (ASCA) in spondyloarthropathies: a reassessment - DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2008)
Objectives. Seronegative spondyloarthropathies, especially ankylosing spondylitis (AS), is shown to be associated with inflammatory bowel disease. Anti-Saccharomyces cerevisiae antibodies (ASCA) is a valid serological marker for Crohns disease. Presence of ASCA is controversial in AS. In this study, we aimed to investigate the prevalence of ASCA in spondyloarthropathies and its relationship with disease activity and severity. Methods. One hundred and seventy-five patients with AS, 47 patients with undifferentiated spondyloarthropathy (uSpA) and 103 healthy controls (HCs) were studied. All patients were questioned for demographic features and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores. Radiological damage is assessed by Bath Ankylosing Spondylitis Radiology Index (BASRI) and modified Stroke Ankylosing Spondylitis Spinal Score (mSASSS). ASCA levels were measured with standard ELISA kits. Results. There was an overall increased prevalence of ASCA IgA in AS and uSpA compared with HCs (20.6 and 19.1% vs 5.8, P= 0.0008 and P= 0.02, respectively). No association was observed between ASCA positivity and erythrocyte sedimentation rate, C-reactive protein levels and BASDAI scores. However, ASCA-positive patients had higher BASRI scores [median BASRI: 7 (2-12) vs 6 (2-12); P=0.037]. Although not reaching significance, they also had reduced chest expansion and higher Bath Ankylosing Spondylitis Functional Index (BASFI) scores. ASCA-positive AS patients also required anti-tumour necrosis factor therapy more frequently (P=0.006). Conclusions. ASCA IgA seems to be more prevalent in AS and uSpA. ASCA can also be a marker of radiological damage and a more severe course in AS.
Keywords: ASCA; spondyloarthropathies; radiographic assessment; severity; INFLAMMATORY-BOWEL-DISEASE; ANKYLOSING-SPONDYLITIS; CROHNS-DISEASE; ULCERATIVE-COLITIS; PREVALENCE; AUTOANTIBODIES; FREQUENCY; CRITERIA; MARKERS